Comparison of the Effects of Seated, Supine, and Walking Interset Rest Strategies on Work Rate. Issue 12 (December 2016) - Ouellette, Kristen A.; Brusseau, Timothy A.; Davidson, Lance E.; Ford, Candus N.; Hatfield, Disa L.; Shaw, Janet M.; Eisenman, Patricia A.
Abstract : Abstract: Ouellette, KA, Brusseau, TA, Davidson, LE, Ford, CN, Hatfield, DL, Shaw, JM, and Eisenman, PA. Comparison of the effects of seated, supine, and walking interset rest strategies on work rate. J Strength Cond Res 30(12): 3396–3404, 2016—The idea that an upright posture should be maintained during the interset rest periods of training sessions is pervasive. The primary aim of this study was to determine differences in work rate associated with 3 interset rest strategies. Male and female members of the CrossFit community (male n = 5, female n = 10) were recruited to perform a strenuous training session designed to enhance work capacity that involved both cardiovascular and muscular endurance exercises. The training session was repeated on 3 separate occasions to evaluate 3 interset rest strategies, which included lying supine on the floor, sitting on a flat bench, and walking on a treadmill (0.67 m·s −1 ). Work rate was calculated for each training session by summing session joules of work and dividing by the time to complete the training session (joules of work per second). Data were also collected during the interset rest periods (heart rate [HR], respiratory rate [RR], and volume of oxygen consumed) and were used to explain why one rest strategy may positively impact work rate compared with another. Statistical analyses revealed significant differences ( p ⩽ 0.05) between the passive and active rest strategies, with the passive strategies allowing for improved work rate (supine = 62.77 ± 7.32, seated = 63.66 ± 8.37, and walking = 60.61 ± 6.42 average joules of work per second). Results also suggest that the passive strategies resulted in superior HR, RR, and oxygen consumption recovery. In conclusion, work rate and physiological recovery were enhanced when supine and seated interset rest strategies were used compared with walking interset rest.